Direct biogas methanation at moderate pressure: Mechanism investigation over Ni-based catalysts - Ilenia Giarnieri; Sining Chen; Daniel Ballesteros-Plata; Juan P. Holgado; Francesco Maluta; Alfonso Caballero; Francesca Ospitali; Enrique Rodríguez-Castellón; Giuseppe Fornasari; Andrew M. Beale; Patricia Benito (Journal of CO2 Utilization)
Direct upgrading of biogas by CO2 methanation aims to produce a gas to be injected into the grid. Operating at moderate pressures favors thermodynamics, but catalyst surface and reaction mechanism under realistic conditions are not well investigated. We study the role of basic and metallic sites on performance and mechanism of clean biogas methanation (CO2/CH4=1/1 v/v) at 1, 5 and 7 bar. Ni/Mg/La/Al hydrotalcite-derived catalysts, with different Ni and La contents, are investigated combining tests and physico-chemical characterization, including quasi-in situ XPS at 7 bar, with CO2-adsorption and methanation DRIFTS at 1 and 7 bar, respectively. An optimized catalyst (6.5 wt% La, 35 wt% Ni) with 3–4 nm Ni0 and balanced basicity, achieves 96 LCH4*gcat−1* h−1 (300°C, 7 bar). DRIFTS confirm catalysts activity experimental trend. Optimizing Ni and La results in higher consumption rates of formate intermediate and sufficient Ni0 sites for CO formation. Increasing pressure to 7 bar promotes CO and m-HCOO reactivity.